Social and economic dimensions of land degradation and desertification - Theodoros Iosifides; George Korres (European Regional Science Association (ERSA), 2002)
The paper is a theoretical discussion and analysis of the relations between socio-economic policies, land use change and desertification in four countries of Southern Europe: Greece, Italy, Spain and Portugal. The discussion is based on preliminary findings of an international research programme (Policies for Land Use to Combat Desertification and Medaction). In most cases the phenomena of land degradation and desertification are researched and seen through their biophysical manifestations, dimensions and consequences despite the fact that it is widely recognized that they are mainly socially driven. The paper explores how land use change may cause or become a tool of combat against desertification and land degradation and discusses a series of possible impact of social and economic policies on the primary driving forces of land use change. These driving forces include population structure and change, administrative and spatial organization, economic development, regional disparities, market and property regimes, social welfare, employment, migration, social exclusion and poverty. The analysis of the possible impact of social and economic policies on the main driving forces of land use change and desertification focuses on the above mentioned Southern European countries, taking into account their participation in the European integration process. The main scope of this analysis is to open up a debate on the actual role of current socioeconomic policy direction on sustainability, land degradation and desertification.
Keywords: 330